PERAN HUMAN RESOURCES DEPARTEMENT (HRD) DALAM MENGEMBANGKAN FUNGSI CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN ETIKA ISLAMI DALAM ORGANISASI - Komala, Cucu (Universitas Muhammadiyah Prof DR HAMKA, 2021)
Human resource development (HRD) is increasingly expected to play a facilitative role in sustainable corporate social responsibility and ethics in organizations. However, there is also significant skepticism regarding HRD's ability to make contributions to these fields. The company's value will grow in a sustainable manner if the company does not only pay attention to profitability but also guarantees the company's social and environmental dimensions. The role of HRD is criticized for moving away from its mission to advocate human values